Go Green Program Management In Community-Based Environmental Conservation In Kampung Wisata Glintung - Sulistiana, Ayu Amanda; Akiriningsih , Titik; Pradipta , Made Prasta Yostitia (Universitas Terbuka, 2025)
This research looks at how the community in Kampung Glintung Go Green, Malang City, has been empowered and how well the community-based environmental conservation efforts have been managed. The study uses a descriptive qualitative approach, gathering information through observations, interviews, and documentation. The findings show that community empowerment in Kampung Glintung Go Green includes organizing structures, providing training and education, encouraging active participation, supporting cooperatives and the local economy, spreading awareness through socialization and campaigns, and setting up systems for monitoring and evaluation, along with building partnerships. The environmental management involves using technology and new ideas, promoting urban farming, educating and involving the community, and working together for economic empowerment, all supported by strong partnerships. While the program has improved environmental quality and community awareness, it is suggested to boost educational efforts, strengthen partnerships, make better use of technology, conduct regular evaluations, and enhance promotion and socialization. This research helps to better understand how Community-Based Tourism (CBT) concepts, environmental conservation strategies, waste management, and partnership models can be applied and could serve as a guide for similar programs in other areas